Surgical treatment and dilemmas in the treatment of basal cell carcinomas with intracranial propagation - Rasulić, Lukas G.; Jovanović, Milan D. (Vojnosanitetski pregled, 2014)
Background/Aim. Basal cell carcinoma (BCC) is one of the most common malignant skin tumors on the head in 90% of cases and is characterized by a high local infiltrating potential and destructive growth.  The aim of this study was to show the characteristics of a correlation between pathohistological types of basal cell carcinoma and the size of this lesion, aggressiveness and infiltration of basal cell carcinoma, and its effect on the course of the therapy. Methods. We analyzed 27 patients operated on for BCC that affected the scalp and the bone. We described and considered the clinical characteristics (size, depth of invasion), duration and speed of intracranial propagation and then made comparison with the type of BCC. We described the extent of surgical treatment and the width of excision to determine the best course of the treatment. The patients went through examinations during the next three years. Results. According to the histopathological type the most common tumors were: infiltrative (60.2%), noduloinfiltrative (37.2%), and morpheaform (2.6%). Tumors were clinically manifested as ulcerative lesions, ulcus rodens and ulcus terebrans. Tumor diameters ranged from 2 to 25 cm. The depth of intracranial propagation depended on the histological type and tumor size. Most relapses (35%) occurred with morpheaform type of BCC. In 17 of the cases, BCC affected the bone without intracranial propagation. In 10 of the cases, basalioma infiltrated intracranial space – in 8 of the cases it infiltrated the dura and in 6 of the cases the brain parenchyma, of which in two of them, the superior sagittal sinus was affected and had to be surgically tied off. Conclusion. The aggressiveness and infiltration of basal cell carcinoma into the brain parenchyma is directly linked to the histological type and the size of the tumor. The larger the basalioma or if histopathological findings confirm morpheaform type of basalioma the larger surrounding healthy tissue, sometimes more than 3 cm in diameter, needs to be removed. In cases of these tumors postoperative radiotherapy is recommended.
Keywords: head and neck neoplasms; neoplasms; basal cell; neoplasm invasiveness; neurosurgical procedures